Elite athletes have significantly elevated serum bilirubin concentrations - Woronyczová, J.; Nováková, M.; Lenícek, M.; Bátovský, M.; Bolek, E.; Cífková, R.; Vítek, L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Bilirubin is a potent endogenous antioxidant and immunomodulating substance, implicated also involved in cell signalization and various metabolic pathways. Mild elevation of its systemic concentrations provides substantial protection against numerous oxidative stress and inflammation-mediated diseases. Rare reports in the literature suggest that serum bilirubin might also be relevant to physical performance. The aim of the current study was to evaluate serum bilirubin concentrations and prevalence of Gilbert syndrome in elite athletes.